Polymer compositions on kinetic resolution of secondary alcohols using polymer-supported silyl chlorides. Issue 31 (13th July 2020) - Zhang, Tian; Dickerson, Shelby D.; Zhu, Tianyu; Tang, Chuanbing; Wiskur, Sheryl L.
Abstract : Modulating the polarity of the polymer backbone affects the selectivity of asymmetric silylation. Abstract : A study of polymer compositions and how they affect the asymmetric kinetic resolution of racemic secondary cyclic alcohols was undertaken to understand the effect of polymer polarity and spacing on the enantiomeric selectivity. Polystyrene-supported silyl chlorides are spatially incorporated with polar methacrylate monomers into the backbone adjacent to the silyl chlorides through controlled RAFT polymerization. The polar compositions in polymers result in significantly higher selectivity factors than the non-polar counterparts, being more comparable to a small molecule system.